Prevalence of behavioural cardiovascular risk factors in Perm Region population - N. S. Karpunina; A. V. Tuev; G. G. Gizatullina (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of behavioural risk factors (RFs) in the Perm Region population. Material and methods. Across 36 areas of Perm Region, 1868 people (810 men, 42,3 %) participated in the questionnaire survey. Mean age of the respondents was 52,3±5,78 years; 36 % of the participants were aged under 30 years, 38,8 % — from 31 to 55 years, and 25,2 % — over 55 years. Results. The majority of male and female respondents self-assessed their health as “satisfactory”. Prevalence of smoking and sedentary lifestyle was 70,5 % and 44,2 %, respectively. Health diet awareness was low; 70 % of young respondents reported never being advised on diet modification. Doctor, as a main source of information on healthy diet, was identified by 7 % and 26 % of the younger and older respondents, respectively. High blood pressure (BP) was registered in 700 participants (42,8 %). Almost 50 % of the respondents reported having their cholesterol measured, but cholesterol levels were known only by every fourth participant (26,6 %). Hyperglycemia awareness was very low, reaching only 10,2 % among all participants with high blood glucose levels. Conclusion. Modifiable RFs, such as low physical activity, smoking, unhealthy diet, and alcohol, remain an important healthcare problem, together with low healthy lifestyle awareness. Active participation of local health professionals in health promotion, counseling, and education is necessary to tackle this problem.